Interest rates, house prices, fertility, and the macroeconomy - Ermanno Affuso; Khandokar Istiak; James L. Swofford (Journal of Risk and Financial Management, 2022)
This study differentiates between housing wealth and financial wealth and investigates whether changes in house prices and changes in interest rates have positive effects on the fertility rate. The study uses U.S. data between 1975-2020, a structural VAR model, and a Toda-Yamamoto causality test to perform the empirical investigation. The results show that changes in house prices and interest rates have a significant positive effect on changes in the fertility rate. The causality test finds that unidirectional causality exists between house prices and interest rates and fertility. The results indicate that children are consumer durable goods. The study predicts that a high fertility rate could be a by-product of an easy monetary policy through the channel of high house prices.
Keywords: 650; fertility; heterogeneous wealth; house prices; structural vector autoregression; Toda– Yamamoto causality test